Dynamic nuclear polarization with simultaneous excitation of electronic and nuclear transitions - Morley, G; Porfyrakis, K; Ardavan, A; Van Tol, J (2008)
Dynamic nuclear polarization transfers spin polarization from electrons to nuclei. We have achieved this by a new method, simultaneously exciting transitions of electronic and nuclear spins. The efficiency of this technique improves with increasing magnetic field. Experimental results are shown for N@C 60 with continuous-wave microwaves, which can be expected to produce even higher polarization than the corresponding pulsed techniques for electron spins greater than 1/2. The degree of nuclear polarization in this case can be easily monitored through the intensities of the well-resolved hyperfine components in the electron paramagnetic resonance spectrum. The nuclear spin-lattice relaxation time is orders of magnitude longer than that of the electrons. © 2008 Springer-Verlag.